Monarch butterflies reared under autumn‐like conditions have more efficient flight and lower post‐flight metabolism. (16th December 2019) - Schroeder, Hayley; Majewska, Ania; Altizer, Sonia
Abstract : 1. Many migratory animals undergo physiological and behavioural changes to prepare for and sustain long‐distance movements. Because insect migrations are common and diverse, studies that examine how migratory insects meet the energetic demands of long‐distance movements are badly needed. 2. Monarch butterflies ( Danaus plexippus ) migrate up to 4000 km annually from eastern North America to wintering sites in central Mexico. Autumn generation monarchs undergo physiological and behavioural changes in response to environmental cues to initiate migration. In particular, exposure to cooler temperatures and shorter day lengths in early autumn causes monarchs to enter the hormonally induced state of reproductive diapause. 3. This study examined differences in flight‐associated metabolic rate (MR) and flight performance metrics for monarchs experimentally reared under autumn‐like conditions (typically experienced before the southward migration) relative to monarchs reared under summer‐like conditions. 4. Adult monarchs reared under autumn‐like conditions showed lower post‐flight MRs, greater flight efficiency, and lower measures of reproductive activity relative to monarchs reared under summer‐like conditions. Increases in post‐flight metabolism were associated with monarch body weight, age, and flight velocity. 5. These findings suggest that a trans‐generational shift in flight energetics is an important component of the monarch's complex migratory syndrome, and that physiological changes that accompany reproductive diapause facilitate energy conservation during flight. Abstract : Environmental conditions are critical for inducing physiological changes associated with insect migration. Monarch butterflies reared under autumn‐like conditions (to induce a migratory state) showed greater flight efficiency and reduced post‐flight metabolic rate relative to monarchs reared under summer‐like conditions. These findings suggest a trans‐generational shift in flight energetics as part of the monarch's complex migratory syndrome.